Biocomputational Prediction of Anticancer Activity of Ayurvedic Plants Inhibiting Cyclin D1: Molecular Docking Study of the Major Active Compounds of Licorice Root Extract (Glycyrrhiza glabra) in Inhibiting Oral Squamous Cell Carcinoma Proliferation - Iqbal, Mohammad (Indonesian Journal of Cancer, 2025)
Background: Oral squamous cell carcinoma (OSCC) reported for 90% of oral cancer cases, causing 377,713 new cases and 177,757 deaths in 2020. Treatments like surgery, chemotherapy, and radiotherapy affect patients’ lives. This study focuses on Licorice (Glycyrrhiza glabra) as an antineoplastic candidate targeting cyclin D1, crucial for cell proliferation in OSCC. It aims to predict licorice root extract (LRE) molecular mechanism against cyclin D1 and identify its most potent antineoplastic compound.Method: The observational research employs a 2D biocomputational method. Ligand and enzyme require 2D isolation, human enzymes at 2–4 Å resolution, and 90% favorable regions. LRE and cyclin D1 are acquired from PubChem, RCSB PDB, PyMol, and Biovia. PyRx performs molecular docking, yielding quantitatively ∆Gbind values in kcal/mol, which indicate anticancer potency (lower values signify better efficacy).Results: All common active compounds of LRE that have negative ∆Gbind values show that this compound can form bonds with the active site of cyclin D1 and inhibit its performance. The results of the molecular docking simulation also showed that 3 of the 9 LRE compounds had lower binding affinity values compared to the abemaciclib control, including glycyrrhetinic acid, liquiritin apioside, and 18β-glycyrrhetinic acid. These three compounds have binding affinity values of -5.5 kcal/mol, -5.3 kcal/mol, and -5.4 kcal/mol, respectively the most effective as an antineoplastic is glycyrrhetinic acid. Conclusion: LRE had potential as antineoplastic against OSCC through cyclin D1 inhibition with the best being glycyrrhetinic acid.